Spatial contagion between stock markets in Central Europe - Anna Czapkiewicz; Tomasz Wójtowicz (Managerial Economics)
In this paper, we investigate contagion between three European stock markets: those in Frankfurt, Vienna, and Warsaw. Two of them are developed markets, while the last is an emerging market. Additionally, the stock exchanges in Vienna and Warsaw are competing markets in the CEE region. On the basis of daily and intraday returns, we analyze and compare the dependence between the major indices of these markets during calm and turbulent periods. A comparison of the dependence in the tail and in the central part of the joint distribution of returns (via a spatial contagion measure) indicates strong contagion among the analyzed markets. Additionally, the application of a conditional contagion measure indicates the importance of taking into account the situation on other markets when contagion between two markets is considered.